PENDIDIKAN AGAMA DI SEKOLAH UMUM KURUN WAKTU 2003 s.d. 2014 - Mulkeis Mulkeis (IAIN Padangsidimpuan, 2015)
Abstract: Islamic education is a subject that gives the basics of Islamic religious knowledge to the learners. Through Islamic Education students will be expected to have faith and devotion to Allah., Virtuous noble character (moral noble), and have sufficient knowledge of Islam that has resistance at the same time can have a power filter to a variety of negative effects arising from the environment. However, the current reality shows that such expectations not reached its full potential. This is partly visible from the declining interest and motivation of learners studying Islamic education and the decline in religious practice learners in everyday life, for example lazy conducting worship, fight or not to obey their parents and teachers, fighting with fellow learners, lazy learning etc. Various problems and challenges faced in the implementation of Islamic religious education require introspection of all stakeholders in an effort to make improvements, so that the objectives of Islamic religious education in schools can be achieved optimally. It required sinergivitas of all related components, especially the Ministry of Religious Affairs, Ministry of Education and Culture and Local Government to make the perception of the implementation of Islamic religious education in schools.Keywords: Education, moral values, Islamic Religious. Abstrak: Pendidikan Islam adalah subjek yang memberikan dasar-dasar pengetahuan agama Islam kepada peserta didik. Melalui Pendidikan Islam siswa akan diharapkan memiliki keimanan dan ketaqwaan kepada Allah. Akhlak mulia (moral yang mulia), dan memiliki pengetahuan yang cukup tentang Islam yang memiliki ketahanan pada saat yang sama dapat memiliki daya filter untuk berbagai efek negatif yang timbul dari lingkungan. Namun, kenyataan saat ini menunjukkan bahwa harapan tersebut tidak tercapai secara maksimal. Hal ini sebagian terlihat dari menurunnya minat dan motivasi peserta didik belajar pendidikan Islam dan penurunan peserta didik praktek keagamaan dalam kehidupan sehari-hari, misalnya ibadah melakukan malas, melawan atau tidak mematuhi orang tua dan guru mereka, berkelahi dengan sesama peserta didik, malas belajar dll. Berbagai masalah dan tantangan yang dihadapi dalam pelaksanaan pendidikan agama Islam membutuhkan introspeksi dari semua pemangku kepentingan dalam upaya untuk melakukan perbaikan, sehingga tujuan pendidikan agama Islam di sekolah-sekolah dapat dicapai secara optimal. Untuk itu diperlukan sinergivitas dari semua komponen terkait, khususnya Kementerian Agama, Kementerian Pendidikan dan Kebudayaan dan Pemerintah Daerah untuk membuat persepsi pelaksanaan pendidikan agama Islam di sekolah-sekolahKata Kunci: Education, moral values, Islamic Religious